The effectiveness of tiktok social media on the consumptive behavior of UMS Communication Science students - Ezra Dewangga Prasaja P; Budi Santosa (Jurnal Mantik, 2023)
Humans have several needs that must be met in living life, but with the advancement of technology, communication, and industry, the current shopping system is more accessible and affordable, namely shopping through social media, Tiktok Shop helps users sell and buy products from the Tiktok application, but over time human needs for goods and services will change, these changes are caused by the nature of humans to be dissatisfied with what is obtained. The purpose of this study is to determine how influential TikTok social media is and the factors that influence consumptive behavior. Respondents in this study are UMS Communication Science Students who use the Tiktok application in their daily lives. The sampling technique used by researchers is purposive sampling. Based on the results of the simple linear regression test, the results of the constant (a) of 15.943 and the regression coefficient (b) of 0.791 are obtained, which means that the variable use of TikTok has an influence on consumptive behavior, from the simple linear test it can be concluded that Ha (alternative hypothesis) is accepted, because the significance value obtained is 0.000 <0.05, which means that the variable use of TikTok (X) has a positive effect on the consumptive behavior variable (Y).